Efficacy of mengkudu leaves extract (morinda citrifolia) on wound healing rate post tooth extraction in white rats (rattus norvegicus) - Irfan Rasul; Desy Setiady (Journal of Dentomaxillofacial Science, 2018)
Objective:Â  This study aims to determine the efficacy of mengkudu leaves extract to accelerate wound healing post tooth extraction in white rats.Material and Methods: Laboratory experimental study was carried out using post-test only and control group design. This study was measured by observing the duration of wound healing post tooth extraction, starting from the formation of sockets after tooth extraction until the socket closed, with sample of 27 white rats in three study groups in accordance with inclusion and exclusion criteria that have been determined.Results: The average healing time in the negative control group is 19 days, the positive control group is 9 days, and the treatment group with mengkudu leaves extract is 7 days. Therefore, the fastest time of wound healing occurs in the treatment group, followed by the positive control group and lastly, in the negative control group.Conclusion: Mengkudu leaves accelerate wound healing post tooth extraction in white male rats.